Spatial distribution and life history traits of two sympatric, cryptic species of sole in the Adriatic Sea basin - SABATINI, LAURA; DONATO, FORTUNATA; LA MESA, MARIO; SCARCELLA, GIUSEPPE; FANELLI, EMANUELA (Mediterranean Marine Science, 2025)
The common sole, Solea solea (Linnaeus, 1758), one of the main fishery demersal resources in the Mediterranean, coexists in the Adriatic Sea with the Egyptian sole, Solea aegyptiaca (Chabanaud, 1927), which is a congeneric and cryptic species. This study, for the first time in this basin, investigated the spatial distribution of the Egyptian sole by combining all data available from fishery dependent and independent sampling activities and comparing certain life history traits of the two sole species. The Egyptian sole was common in the north-western coastal waters, with a concentration area of juveniles around the Po River mouth and larger individuals on medium sandy sediments associated with ancient delta systems in the central part of the Gulf of Venice. The hypothesis posits that these areas serve as essential habitats for the Egyptian sole. The two sole species exhibited similar characteristics, with positive allometric growth and sexual dimorphism. An analogous growth trend was observed during ontogeny, characterized by fast growth until the second year of life, with maximum size achievement starting from the third year of life. Both species have the potential to attain lifespans exceeding 10 years. All these analogies confirmed their classification as cryptic species. The hypothesis posits that the two species rely on olfactory sense rather than visual signals for intraspecific recognition. This study represents an initial endeavor to elucidate the characterizing traits and habits that enable these two sibling soles to coexist as distinct species, thereby providing useful information to support resource assessment and management in the Adriatic Sea.